2014
DOI: 10.1073/pnas.1408759111
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of alphavirus M1 as a selective oncolytic virus targeting ZAP-defective human cancers

Abstract: Oncolytic virotherapy is a growing treatment modality that uses replicating viruses as selective antineoplastic agents. Safety and efficacy considerations dictate that an ideal oncolytic agent would discriminate between normal and cancer cells on the basis of common genetic abnormalities in human cancers. Here, we identify a naturally occurring alphavirus (M1) as a novel selective killer targeting zinc-finger antiviral protein (ZAP)-deficient cancer cells. In vitro, in vivo, and ex vivo studies showed potent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 45 publications
7
124
0
1
Order By: Relevance
“…Moreover, data mining of the gene array data in the GEO database found that in the alphavirus M1 susceptible human hepatocellular carcinoma cell line Hep3B, FAT10 was significantly upregulated (332-fold) as compared with the alphavirus M1 resistant human fetal hepatic cell line L-02 (GEO accession number Fig. 1C) (38). In addition, another microarray data demonstrated a 2-fold FAT10 upregulation in ribavirin-resistant HCV-infected cell lines compared with the original ribavirin-sensitive HCV RNA-replicating cell line (GEO accession number GSE60948) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data mining of the gene array data in the GEO database found that in the alphavirus M1 susceptible human hepatocellular carcinoma cell line Hep3B, FAT10 was significantly upregulated (332-fold) as compared with the alphavirus M1 resistant human fetal hepatic cell line L-02 (GEO accession number Fig. 1C) (38). In addition, another microarray data demonstrated a 2-fold FAT10 upregulation in ribavirin-resistant HCV-infected cell lines compared with the original ribavirin-sensitive HCV RNA-replicating cell line (GEO accession number GSE60948) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The caspase-3/7 flow cytometry assay kit was from Life Technologies (C10427). The strain of M1 virus has been described in our previous research (5,6), and the virus was grown in the Vero cell line. The titer of virus was calculated by median tissue culture infectious dose assay in BHK-21 cell line.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that cancerselective replication underlies the cancer targeting property of M1 (6,15,16). To understand whether the replication of M1 virus is affected by SMCs, we analyzed the effect of SMCs on the replication of M1 virus.…”
Section: C-iap1 and C-iap2 Play Key Roles In The Enhanced Oncolytic Ementioning
confidence: 99%
See 1 more Smart Citation
“…Besides its antiviral effect, Todorova et al [11] found that ZAP exerts an antitumor effect by binding to cellular RNA to prevent apoptosis induced by tumor necrosis factor-related apoptosis inducing ligand (TRAIL). In our previous study, we found that a decrease of ZAP expression in cancer tissue compared with pericarcinous tissue is common in liver, colon, and bladder cancer [12], suggesting that loss of ZAP may indeed be favorable for the progression of certain cancers. Bioinformatic analysis of the cBioPortal database (http://www.cbioprotal.org) also revealed that HCC exhibits low expression of ZAP mRNA.…”
Section: Introductionmentioning
confidence: 93%